Broad-Spectrum Antiviral Activity of Pyridobenzothiazolone Analogues Against Respiratory Viruses - Elisa Feyles; Tommaso Felicetti; Irene Arduino; Massimo Rittà; Andrea Civra; Luisa Muratori; Stefania Raimondo; David Lembo; Giuseppe Manfroni; Manuela Donalisio (Viruses)
Cell-based phenotypic screening of a privileged in-house library composed of pyridobenzothiazolone (PBTZ) analogues was conducted against representative viruses responsible for common respiratory tract infections in humans, i.e., respiratory syncytial virus (RSV), human coronavirus type OC43 (HCoV-OC43), and influenza virus type A (IFV-A). We identified a compound with broad-spectrum inhibitory activity against multiple strains of RSV, HCoV, and IFV, with EC50 values in the low micromolar range and cell-independent activity. Its antiviral activity and cytocompatibility were confirmed in a fully differentiated 3D model of the bronchial epithelium mimicking the in vivo setting. The hit compound enters cells and localizes homogeneously in the cytosol, inhibiting replicative phases in a virus-specific manner. Overall, the selected PBTZ represents a good starting point for further preclinical development as a broad-spectrum antiviral agent that could address the continuous threat of new emerging pathogens and the rising issue of antiviral resistance.